(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the role and depiction of visual arts carried out by the director in the Lenong folk theater performance titled "Beli Telor," produced by students interested in theater from the Sendratasik Education Study Program, Faculty of Language and Arts, Universitas Negeri Padang. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through literature study, direct observation of the performance, in-depth interviews with the director, as well as documentation of the rehearsal and performance process. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The research results show that the director plays a central role as a leader, communicator, production manager, manager of dramaturgical elements, and visual art director. In depicting visual art, the director applies a presentation concept that is simple yet effective through stage arrangement, lighting setup, makeup, costumes, use of props, and the positioning and movements of the actors (blocking). The directing style applied is a mix of a guided approach and allowing room for improvisation, so it can maintain the unique characteristics of Lenong as a communicative, humorous, and community-centered folk theater while also shaping it into a visually engaging performance. In conclusion, the director’s ability to integrate all elements of a performance is the key factor in successfully realizing Lenong as a visual artwork that still preserves cultural values and the moral message intended.